(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study sought to determine the extent of provision of mentoring services for the professional growth of business educators in tertiary institutions in South East, Nigeria. One research question guided the study and one null hypothesis was tested at 0.05 level of significance. Descriptive survey research design was employed for the study. The population consisted of 188 business educators of colleges of education and universities in South East, Nigeria. There was no sampling as the entire population was studied. The instrument for data collection was a structured questionnaire titled “Mentoring Services for Professional Growth of Business Educators Questionnaire” (MSPGBEQ). The instrument was validated by three experts.Method of internal consistency was used to determine the reliability of the instrument using Cronbach Alpha with SPSS and reliability coefficient of 0.79 was obtained. The data collected were analyzed using descriptive statistics of mean and standard deviation in answering the research question and inferential statistic of ztest for testing the null hypothesis. Data analysis revealed that academic mentoring services were provided at a low extent. The result also revealed that gender was not a significant factor influencing the extent academic mentoring services were provided for business educators’ professional growth in tertiary institutions in South East, Nigeria. Based on the findings of this study, it was concluded that the provision of mentoring services for business educators’ professional growth in South East, Nigeria was inadequate and it was recommended among others that institutions and departments should endeavour to engage the services of research institutions and individual researchers in human resources development for the purpose of acquainting business educators with various mentoring services that would enhance business educators’ professional growth.